Postoperative Analgesia and Recovery Course After Major Colorectal Surgery in Elderly Patients: A Randomized Comparison Between Intrathecal Morphine and Intravenous PCA Morphine. Issue 6 (1st November 2006) - Beaussier, Marc; Weickmans, Henri; Parc, Yann; Delpierre, Eric; Camus, Yvon; Funck-Brentano, Christian; Schiffer, Eduardo; Delva, Eric; Lienhart, André
Abstract : Background and Objectives: Intrathecal morphine is a widely used method for postoperative pain relief after major abdominal surgery. The aim of this randomized, double-blinded study was to compare intrathecal morphine and intravenous PCA morphine for postoperative analgesia and recovery course after major colorectal surgery in elderly patients. Methods: After written informed consent, patients >70 years of age were prospectively and randomly assigned to receive either preoperative intrathecal morphine (0.3 mg) and postoperative patient-controlled (PCA) intravenous morphine (IT morphine) or PCA alone (group control). Results are presented as mean ± SD (95% confidence interval). Results: Twenty-six patients successfully completed the study in each group. In the IT morphine group, rate of awakening was delayed. Pain intensity and daily intravenous morphine consumption were significantly reduced 1 and 2 days after surgery in the IT morphine group ( P < .01). Mental function (assessed by Mini Mental State and Digit Symbol Substitution Test) was similar in both groups. Episodes of postoperative delirium/confusion occurred similarly in both groups. Time to ileus resolution and time to ambulation without assistance did not differ between the 2 groups. The duration of hospitalization was 8.4 ± 1.7 (7-11) days and 7.9 ± 2.0 (6-9.9) days for control and IT morphine, respectively (nonstatistical difference). Patients in the IT morphine group had longer time to awakening from anesthesia and experienced more sedation. Conclusions: Intrathecal morphine, as compared with intravenous PCA morphine alone, improves immediate postoperative pain and reduces parenteral morphine consumption but does not improve postoperative recovery in elderly patients after major colorectal surgery.